Reputation: 175
Suppose that f := x -> k
where k
is a constant. Then sum(f(x), i = 1 .. n)
is nk
. Now suppose that I have a non-constant function of x defined as f := x -> exp(-x)
. Now I have y
defined to be y := product(f(x__i), i = 1 .. n)
and the answer I am getting is wrong which is exp(-x__i)^n
. So it seems like Maple treats every expression or function under the summation to be constant. The correct answer is supposed to be exp(-sum(x__i, i = 1 .. n))
. I am looking for assistance on how to fix this. Below is my MWE:
f := x -> exp(-x);
y := product(f(x__i), i = 1 .. n);
y := simplify(y);
Upvotes: 0
Views: 74